Basic and new concepts of ovarian cyst pathogenesis in cattle (VETERINARIA, 2020)
Ovarian cyst (OC) is one of the major factors affecting the fertility of dairy cows considering its effect on the reproductive performances and the economic losses. In spite of a lot of research, many aspects of OC, especially its pathogenesis remain unclear and not very conclusive. It is well known that a follicle becomes cystic because it doesn’t ovulate. Failure of ovulation is related to the dysfunction of the hypothalamo-pituitary axis, which can have several origins. The refractory state of the hypothalamus to the positive feedback effect of estrogens is related to the presence of intermediate dose of progesterone. At the ovarian level, the data are conflicting as for the cellular and molecular changes including the expression of hormone receptors. The same applies to the other factors which can increase the incidence of OC, in particular the animal or environment-specific with controversial study results. At the end, we can conclude that OC is a complex condition of different origins, which makes research on its pathogenesis still relevant.
Keywords: ovarian cyst; etiopathogenesis; cow